выполните умножение a^3+ba^2/a-b*a^2-b^2/a^2+2ab+b^2*(1/a+1/b). Ответ должен получиться a^2+ab/b.

1

Ответы и объяснения

2013-06-10T19:53:50+00:00

Выражение: a^3+b*a^2/a-b*a^2-b^2/a^2+2*a*b+b^2*(1/a+1/b)

Ответ: a^3+3*b*a-b*a^2-b^2/a^2+b^2/a+b

Решаем по действиям:
1. a^2/a=a
a^2/a=a^(2-1)
1.1. 2-1=1
-2
_1_
1
2. b*a+2*a*b=3*b*a
3. b^2*(1/a+1/b)=b^2/a+b
b^2*(1/a+1/b)=b^2*1/a+b^2*1/b
3.1. b^2/b=b
b^2/b=b^(2-1)
3.1.1. 2-1=1
-2
_1_
1

Решаем по шагам:
1. a^3+b*a-b*a^2-b^2/a^2+2*a*b+b^2*(1/a+1/b)
1.1. a^2/a=a
a^2/a=a^(2-1)
1.1.1. 2-1=1
-2
_1_
1
2. a^3+3*b*a-b*a^2-b^2/a^2+b^2*(1/a+1/b)
2.1. b*a+2*a*b=3*b*a
3. a^3+3*b*a-b*a^2-b^2/a^2+b^2/a+b
3.1. b^2*(1/a+1/b)=b^2/a+b
b^2*(1/a+1/b)=b^2*1/a+b^2*1/b
3.1.1. b^2/b=b
b^2/b=b^(2-1)
3.1.1.1. 2-1=1
-2
_1_
1